The Representation and Participation of Marginalized Voices in the Provincial Parliament in Nepal: Exploring Sustainable Development Strategies - Subedi, Prem (Academia Journal of Humanities & Social Sciences, 2025)
This paper examines the current practices of representation and participation of women and marginalized groups in the parliamentary processes of Gandaki Province Assembly, Nepal, relating to inclusive democracy, intersectionality theories, and Sustainable Development Goals (SDGs) of United Nations (UN). The study used the explanatory sequential mixed methods, using the parliament members as respondents who are elected from the female and marginalized groups. The primary and secondary data collected are analyzed to explore the findings of the study. The findings demonstrated that systemic inequities, with overrepresentation of privileged groups such as Khas-Arya, limited participation of marginalized groups in leadership roles, and biases in committee assignments and decision-making processes. The barriers such as cultural norms, language, and procedural challenges further limit a meaningful participation of women and marginalized groups. Although the proportional representation system has increased women’s presence, dependence on this system emphasizes the inadequacies of the first past the post-system in fostering diversity. Further, the study highlights the perception difference due to intersecting identities of gender and marginalized groups in the assembly. Finally, the paper recommends the structural reforms, leadership training, financial support, and research-based interventions to enhance equitable representation and participation.